Incidentally Discovered Malrotation in a Case of Gastric Perforation - Abhishek Soham Satpathy (New Visions in Medicine and Medical Science Vol. 8, 2024)
Aim: The study is a case report of a 36-year-old male with blunt trauma to the abdomen following a road traffic accident, with an intraoperative finding of gastric perforation alongside an incidentally detected malrotation. Introduction: The term "intestinal malrotation" refers to abnormalities affecting intestinal fixation and intestinal nonrotation or partial rotation around the superior mesenteric artery. Only 0.2 to 0.5% of people exhibit symptoms, with the remainder exhibiting none at all. Case Presentation: A 36-year-old man arrived at the hospital two days ago with traumatic abdominal damage. Examination results showed that the patient had a blood pressure of 90/60 mmHg, a pulse of 130 bpm, a respiratory rate of 32 breaths per minute, and a saturation of 78% in room air. X-ray chest showed gas under diaphragm. An anterior gastric rupture with a transverse colon below the stomach and a jejunum with small bowel loops present on the right was discovered during an emergency laparotomy. Gastrojejunostomy was done. The patient’s postoperative stay went smoothly, and on POD 10, he was discharged, able to resume his regular oral diet and pass stool. Conclusion: Intestinal malrotation is a rare developmental anomaly of the embryonic gut. In babies, bilious vomiting is the most prevalent presentation; in older children and adults, chronic and sporadic abdominal pain is evident. Surgery is debatable in asymptomatic patients. However, adults with delayed malrotation presentation manifest with varied symptoms. Hence, to prevent further difficulties, a high index of suspicion together with pertinent investigations (CT and USG) is required.